Determining The Hemoglobin Levels of Quail (Coturnix coturnix japonica) Using Image Processing from Desktop Scanner - Santoso, Koekoeh; Azizah, Sofa; Widhyari, Sus Derthi; Ulum, Mokhamad Fakhrul; Seminar, Kudang Boro; Suprayogi, Agik (Jurnal Veteriner, 2025)
Various animal diseases require colorimetric-based laboratory diagnose. One of them is the measurement of blood hemoglobin concentration. Anemia needs to be detected as early as possible, because the lack of hemoglobin in the blood could results in a lack of oxygen being carried from the lungs to the tissues. Colorimetry is a quantitative analysis technique for colored samples to determine the concentration of a substance based on the light intensity of the color solution. Colorimetry is commonly used to measure the level of hemoglobin in the blood. Image processing using image J has been widely used for chemical analysis. This study was aimed to determine the potential of image processing from a desktop scanner to measure animal blood hemoglobin. The blood used was taken from five quail. Quail blood was diluted to 100%, 90%, 80%, 70%, 60% and 50% respectively. The results of hemoglobin level readings using the Sahli method were strongly correlated, but significantly different, with a spectrophotometer. The readings of hemoglobin levels using a desktop scanner have a very strong correlation and are not significantly different from the results obtained using a spectrophotometer. The image processing method from a desktop scanner can be used as an alternative to a spectrophotometer to measure blood hemoglobin levels compared to using the Sahli method.